Challenges affecting informal sector tax administration, enforcement and compliance in African countries: Evidence from Zimbabwe - Mpofu, Favourate Y (The Journal of Accounting and Management, 2023)
Taxation is considered globally, a reliable, stable, and more predictable route of mobilising revenue for the government. While the informal sector has grown exponentially in developing countries, its size is not matched by its contributions to the economy. For decades the taxation of this sector has remained controversial. Its enigmatic nature and the complexities involved in making efforts to tax have been contested based on the costs viz-a-viz the benefits derived from taxing the sector. Existing literature is inconclusive on this, and this study sought to unpack the administrative, enforcement, and compliance challenges surrounding informal sector taxation. The study employed a sequential mixed method exploratory research design which supports the collection of qualitative data from various stakeholders using interviews, observation, and document analysis, supported by questionnaires for the quantitative part. This study employed thematic analysis with the aid of NVIVO Pro 12 for interviews and SPSS for questionnaires. Findings reveal that the informal sector’s potential to contribute more is stifled by structural and policy issues embedded in the existing tax systems such as the complexity of tax systems, lack of stakeholder engagement, high tax rates, and aggressiveness of tax authorities. This was further compounded by challenges emanating from the institutional environment and the nature of the sector such as corruption, political interference, bureaucracies in formalisation, and lack of tax knowledge. Therefore, a review of tax policy, stakeholder dialogue, and engagement are recommended to enhance the informal sector’s tax compliance abilities. In addition, the capacity of the tax authority should be extended to both human capital and technological resources.